2021
DOI: 10.1021/acssynbio.1c00024
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Characterization of Coherent Feed-Forward Loop-Based Synthetic Genetic Circuits

Abstract: Regulatory pathways inside living cells employ feed-forward architectures to fulfill essential signal processing functions that aid in the interpretation of various types of inputs through noise-filtering, fold-change detection and adaptation. Although it has been demonstrated computationally that a coherent feed-forward loop (CFFL) can function as noise filter, a property essential to decoding complex temporal signals, this motif has not been extensively characterized experimentally or integrated into larger … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Lehr et al have shown the implementation of CFTS in commercially available cell-free transcription-translation systems (TX-TL) based on cell extracts ( Lehr et al, 2019 ), which are also sourced from the US and shipped under cold chain. Encouragingly, Silverman et al (2019) , McNerney et al (2019) and Pieters et al (2021) have recently shown the successful implementation of CFTS in home-made cell extracts, offering a path for local prototyping de novo sensors of interest ( McNerney et al, 2019 ; Silverman et al, 2019 ; Pieters et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lehr et al have shown the implementation of CFTS in commercially available cell-free transcription-translation systems (TX-TL) based on cell extracts ( Lehr et al, 2019 ), which are also sourced from the US and shipped under cold chain. Encouragingly, Silverman et al (2019) , McNerney et al (2019) and Pieters et al (2021) have recently shown the successful implementation of CFTS in home-made cell extracts, offering a path for local prototyping de novo sensors of interest ( McNerney et al, 2019 ; Silverman et al, 2019 ; Pieters et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… 55 , 56 All of the genetic constructs for the inputs, weights, and the independent reporter were constructed using a Golden Gate assembly-based cloning method. 57 The DNA constructs used were optimized for RNA stability as well as the efficacy of the input–weight pair, as reported by Pieters et al 62 Polymerase chain reactions (PCR) were used to prepare linear DNA templates for use in the experiments (see the Methods section).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, continuous flow reactions can be implemented to provide sufficient transcription and translation resources over prolonged durations. 62 , 77 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plot of intensity against the complex concentration over a 2-h interval obtained a sigmoidal fit with a steep rise between 10 nM and 100 nM (Section S4, Supplementary File S7). This showed that the model is sensitive to changes in the concentration of the trigger miRNA biomarker in the range of interest, satisfying a necessary biosensor property [ 25 , [55] , [56] , [57] , [58] , [59] , [60] ]. A similar trend of sigmoidal kinetics was observed for the hsa-miR-20a-5p biomarker over a complex concentration range of 100 nM and 1 μM (Supplementary File S7).…”
Section: Resultsmentioning
confidence: 99%